Active IC metering of digital signal processing subsystem with two-tier activation for secure split test - Dhabu, Sumedh Somnath (2018)
Active integrated circuit (IC) metering is a class of hardware security protocols that enables the designer to track the number of chips produced from the same mask and remotely activate only the desired ones. This paper reviews existing IC metering approaches to incorporate the advantages of individual methods into a secure functional lock on digital signal processing submodule of wireless communication system to avoid legitimate channel exploitation and the risk of deploying unreliable out-of-specs gray market ICs. Our method makes use of aging-sensitive physical unclonable function to enable a two-tier activation of ICs in split test flow to track chip supply after production tests. Extraneous states are inserted into the state-space mapping of digital signal processing submodule as opposed to controller to provide a stronger state dependency on datapath and input signal. The scheme is illustrated experimentally on a pulse shaping filter of the transmitter for a wireless communication system.